Use of amitriptyline, bupropion and agomelatine in the treatment of non-depressive disorders: a review of mechanisms and therapeutic indications - Czerniak, Piotr; Buszek, Julia; Medygrał, Michał; Koszuta, Przemysław; Dydoń-Pikor, Małgorzata; Pajdak-Gicala, Katarzyna; Kawecki, Maciej; Antoszewska, Adrianna; Bargiel, Weronika; Buszek, Sylwia (Quality in Sport, 2025)
Introduction Antidepressants such as amitriptyline, bupropion and agomelatine are widely used not only in the treatment of depression, but also in other conditions. Their mechanisms of action affect different neurotransmitter systems, allowing their use in the treatment of pain, addiction or sleep disorders. Amitriptyline, which is a tricyclic antidepressant, has strong analgesic effects. Bupropion, a dopamine and norepinephrine reuptake inhibitor, helps in the treatment of addiction and ADHD. Agomelatine, a melatonin receptor agonist, has been shown to regulate diurnal rhythms, making it useful in the treatment of insomnia and other sleep disorders. Aim of the Study The aim of this study is to analyse the use of amitriptyline, bupropion and agomelatine in the treatment of conditions other than depression, with a focus on their mechanisms of action and clinical efficacy. Materials and Methods An analysis of PubMed papers was conducted using keywords: antidepressants, tricyclic antidepressants, SSRI, amitriptyline, bupropion, agomelatine. Basic Results Amitriptyline is highly effective in the treatment of neuropathic pain, migraines and insomnia due to its potent action on serotonin and histamine receptors. Bupropion is used in the treatment of nicotine addiction and ADHD, as it acts on the dopaminergic and noradrenergic systems to improve concentration and impulse control. Agomelatine, as a melatonin receptor agonist, is used to regulate diurnal rhythms, making it helpful in the treatment of sleep disorders and adaptation to time zone changes. Each of these drugs has unique properties that go beyond their primary use in depression.